SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF SILVER NANOPARTICLES - V.Kabila, S. Violet Beaulah, V. Sankara Vel, Sanjana Bhat, A.Sivaranjini, M. I. Niyas Ahamed* (Chelonian Research Foundation, 2023)
Nanoparticles, which are the tiniest components of nanotechnology, are currently exerting a significant influence across multiple domains of our daily existence. The frequent use of antibiotic drugs is responsible for the development of multidrug resistance (MDR) in pathogenic microorganisms, which is a significant obstacle to effectively diagnosing and treating infectious diseases. Nanoparticle-based therapy is a promising method to enhance the effectiveness of systemic therapeutic intervention while minimising its toxicity. Silver nanoparticles (AgNPs) have gained significant attention in the field of biomedicine due to its diverse applications, such as antibacterial therapy, wound dressings, diagnostic and treatment, and contraceptive devices. Therefore, AgNPs are a highly promising therapeutic agent that has the ability to successfully combat numerous microbial diseases, including antibiotic-resistant bacteria. Hence, the creation of a therapy plan centred around AgNPs to amplify the antibacterial impact is an innovative and encouraging method. The utilisation of plant extracts for the production of nanoparticles, known as green synthesis, offers a very effective alternative to the traditional procedures using chemical and physical processes. These conventional methods often result in the generation of environmentally harmful by-products. Keywords: Silver Nanoparticle, Green synthesis, antibacterial activity.